2002
DOI: 10.1002/cjg2.278
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Earthward Propagating Plasmoids

Abstract: The correlation between plasmoids and geomagnetic substorms has been demonstrated by satellite observations. In addition to the tailward propagating plasmoids with N‐S bipolar signatures, earthward propagating plasmoids are found, which are characterized by plasma sheet S‐N bipolar events and lobe S‐N bipolar signatures. The occurrence rate of the S‐N bipolar events is much lower than that of the N‐S events. The S‐N bipolar events occur primarily during quiet geomagnetic and IMF Bz north period, and they are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Deep reflection seismic data were collected on the Manzhouli-Suifenhe geoscience transect (Figure 1b, dashed green line), which crossed the whole of the Northeast China in NW-SE direction (Yang et al, 1996). The 3-5 km Moho offset between the Songliao basin (shallow Moho) in the east and the Greater Xing'an Range (deeper Moho) in the west, has been proposed to be the cause of the north-south trending gravity lineament (Yang et al, 1996). Guo et al (2014) also observed a 4 km Moho offset across the north-south trending gravity lineament with a change from 33 km beneath the Songliao basin to 37 km beneath the Greater Xing'an Range using P wave and S wave receiver function.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep reflection seismic data were collected on the Manzhouli-Suifenhe geoscience transect (Figure 1b, dashed green line), which crossed the whole of the Northeast China in NW-SE direction (Yang et al, 1996). The 3-5 km Moho offset between the Songliao basin (shallow Moho) in the east and the Greater Xing'an Range (deeper Moho) in the west, has been proposed to be the cause of the north-south trending gravity lineament (Yang et al, 1996). Guo et al (2014) also observed a 4 km Moho offset across the north-south trending gravity lineament with a change from 33 km beneath the Songliao basin to 37 km beneath the Greater Xing'an Range using P wave and S wave receiver function.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…In the interpretation presented below, estimates of Moho depth from published seismic studies are used. Deep reflection seismic data were collected on the Manzhouli‐Suifenhe geoscience transect (Figure 1b, dashed green line), which crossed the whole of the Northeast China in NW‐SE direction (Yang et al., 1996). The 3–5 km Moho offset between the Songliao basin (shallow Moho) in the east and the Greater Xing'an Range (deeper Moho) in the west, has been proposed to be the cause of the north‐south trending gravity lineament (Yang et al., 1996).…”
Section: Interpretation and Discussionmentioning
confidence: 99%